GEOGRAPHICAL DISTRIBUTION AND PROTECTION OF BIRDS IN FERGANA VALLEY (Scientific journal of the Fergana State University, 2023)
In this article, on the basis of literature data and authors research geographical wide spread of birds and their protection in the Ferganа valley are given.